Pengaruh Peran Guru dan Gaya Pengasuhan Orang Tua Terhadap Pembentukan Karakter Siswa: Sebuah Studi Kuantitatif - Sumartini, Sri (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This study aimed to investigate the influence of teacher roles and parenting styles on student character formation at Madrasah Ibtidaiyah Negeri 2 Sleman Yogyakarta using a quantitative associative research method. Multiple linear regression analysis showed that both factors significantly influenced student character formation, with parenting style having a higher contribution than teacher roles. Therefore, a balanced approach between education at home and school is necessary to support good character formation among students. The resulting multiple linear regression equation was Y = 14.047 + 0.497X1 + 0.910X2, with a determination coefficient of 55.9%. Parenting style contributed more (?= 0.910) than teacher roles (?= 0.497) by 58.87%. However, the study had limitations, such as focusing on one school and specific geographical context. Therefore, it is recommended to conduct similar studies in different schools and regions and explore other factors that may influence student character formation.